TEACHING READING USING CIRC METHOD: THE CHALLENGES AND THE BENEFITS - Brigitta Septarini Rahmasari; Agnes Ery Swasti (UIBU, 2022)
The research objectives are describing the use of the CIRC (Cooperative Integrated Reading Comprehension) method to teach reading and finding the strengths and weaknesses of CIRC to teach reading to young learners. This research is applied in qualitative research with a descriptive analysis model. The data collecting is done by observation, interview, and documentation. In analyzing data, it is done by data reduction, data display, and conclusion drawing and verification. The result of this research shows the implementation of CIRC Method to teach reading are: (1) partner reading, (2) story grammar and related writing (3) word out loud, (4) word meaning, (5) story retell, and (6) spelling. Meanwhile, the advantages of CIRC method in teaching reading are first, the students are easy to understand the material. Second, the students have the motivation to learn to read more. Third, the situation of the class is fun. Fourth, students pay more attention and are more focused on learning. Besides, the challenge of CIRC method in teaching reading is sometimes the students are confused by the teacher’s explanation and instruction.